Re-Evaluating Biologic Pharmacotherapies That Target the Host Response during Sepsis - Tuttle, Kristopher M. (Int J Mol Sci, 2019)
Multiple organ dysfunction syndrome (MODS) caused by the systemic inflammatory response during sepsis is responsible for millions of deaths worldwide each year, and despite broad consensus concerning its pathophysiology, no specific or effective therapies exist. Recent efforts to treat and/or prevent MODS have included a variety of biologics, recombinant proteins targeting various components of the host response to the infection (e.g., inflammation, coagulation, etc.) Improvements in molecular biology and pharmaceutical engineering have enabled a wide range of utility for biologics to target various aspects of the systemic inflammatory response. The majority of clinical trials to date have failed to show clinical benefit, but some have demonstrated promising results in certain patient populations. In this review we summarize the underlying rationale and outcome of major clinical trials where biologics have been tested as a pharmacotherapy for MODS in sepsis. A brief description of the study design and overall outcome for each of the major trials are presented. Emphasis is placed on discussing targets and/or trials where promising results were observed. Post hoc analyses of trials where therapy demonstrated harm or additional risk to certain patient subgroups are highlighted, and details are provided about specific trials where more stringent inclusion/exclusion criteria are warranted.